СПАЙК БІЛОК SARSCOV2 ПІДВИЩУЄ ЕКСПРЕСІЮ CXCR4 ТА МІГРАЦІЮ КЛІТИН РАКУ МОЛОЧНОЇ ЗАЛОЗИ IN VITRO - Shlapatska, L.; Abramenko, I.; Zavelevich, M.; Brichenko, V.; Chumak, A.; Buchynska, L. (PH Akademperiodyka, 2026)
Background. There are some data that viral respiratory infections facilitate metastasis of breast cancer (BC). However, whether the coronavirus SARS-CoV-2 is a trigger for BC progression is not yet clear, as well as the possible mechanisms of its involvement. Aim. The work aimed to study the effect of the SARS-Cov-2 spike protein (SP) on the expression profile of components of the CXCL12/CXCR4 key signaling аxis of BC, cell adhesion markers CD326, CD54, epithelial cells cytokeratin-18 and b-catenin, and migratory activity in in vitro model system. Materials and Methods. The expression profile of the studied markers was detected by flow cytometry after 48 h of incubation of MCF-7 and MDA-MB-231 cells with SP. Marker expression was assessed by the number of positive cells (%) and the level of its expression (the relative index of mean fluorescence intensity of cells, iMFI). Cell migration was analyzed by the scratch assay. Results. After SP treatment, a significant increase in CXCR4 expression was detected in the cytoplasm of both MCF-7 and MDA-MB-231 cells. SP caused opposite effects on CXCL12 expression — an increase in the MDA-MB-231 cells and decrease in the MCF-7 cells. In addition, in MCF-7 cells, SP treatment resulted in a decrease in the number of CD54-positive cells, the iMFI of CD326, cytokeratin-18, and a slight increase in the iMFI of b-catenin, while in the MDA-MB-231 cell line, a significant decrease in the iMFI of CD54 was observed. SP accelerated the migration activity of MDA-MB-231 and MCF-7 cells, the effect being more pronounced in MDA-MB-231 cells. Conclusion. The immunophenotypic changes in the expression profile of several markers under the influence of SP may indicate the induction of the epithelial-mesenchymal transition in the MCF-7 cells and increased migration activity in both cell lines.